(3TQM GdeNJUQ GdfGaYs - (3eLghds
(3ChdgG (B:s
(3MeOG ddg (B... (3abO CedjJ dcJGH GdehGQjK ef cJGH GdfGaY GdefJNH ef GdTQGFY cdeGJ JLQj dg eLQi GdTQM heGdG jVGgjg (B.. (3cJGH GdehGQjK ; GYde Cf GdehGQjK CYe ef GdaQGFV JYe GdhQGKI HGdaQV hHGdbQGHI dG jbY EdG Ydi GdSgGe GdSJ GdePchQI (B...s
(3BNQgG (B:s
... (3hCf CHhg SHH ehLH ddejQGK aGOYGg SahWg HGdHQ JMJGL Edi Odjd bGY hdG Odjd Ydjg Hd ggfG eG jbJVj HWdGfg dGfg GSbGW Mb de jKHJ HYO hebd Pdc dG jdaJ Edjg TQYG (B.. (3bO aQZJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis